LATIHAN KEBUGARAN JASMANI TERHADAP MOTIVASI MEMBER FITNES LIFE SOGO GYM - Ella Anugrarista; Arisman Arisman; Noer Riswandi (Jurnal Pendidikan Olah Raga, 2022)
The purpose of this research Â was to determine the motivation of the fitness center members for physical fitness training at Life Sport GYM Ngabang members in 2019. This research was a descriptive research. This research was conducted at Life Sport GYM Ngabang on July 27th, 2019. The sample in this was was 21 fitness members. The sampling technique uses purposive sampling technique. The data analysis used was descriptive statisticsThe results of this research was the motivation of members fitness center in doing physical fitness training to the members of Life Sport GYM Ngabang in 2019 was obtained by the motivation level of fitness members doing physical fitness exercises with a total internal motivation score of 1561 (49.55%) and greater than with extern motivation that is obtained a score of 924 (29.33%). Thus, the level of motivation in fitness members at Sogo Gym Ngabang in 2019 bothÂ  for motivation from intern and motivation from extern with an overall score of 2485 (78.88%) with a good category.